2021
DOI: 10.1186/s13063-021-05143-6
|View full text |Cite
|
Sign up to set email alerts
|

Study factors associated with the incompletion of clinical trials that include pediatric patients: a retrospective analysis of the European Clinical Trials Database and a lesson from the European region

Abstract: Background Incomplete clinical trials for pediatric drug development result in a lack of adequate scientific evidence for providing appropriate medication to pediatric populations; this is especially true for Japan. Thus, using the European Clinical Trials Database (EudraCT), this study aimed to identify the factors related to the study design and administration that lead to incompletion of clinical trials that included pediatric patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In 2021, an analysis by Tanemura et al from the European Clinical Trials Database (EudraCT) suggested that incomplete pediatric trials are primarily associated with the phase of trial design, feasibility, and country eligibility. Low recruitment rate was related to the selection of sites and/or countries with lack of infrastructure and difficult communication (5). These factors led to insufficient scientific evidence for labeling and/or adjusting clinical use of drugs, resulting in a persistently high off-label drug use in children (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, an analysis by Tanemura et al from the European Clinical Trials Database (EudraCT) suggested that incomplete pediatric trials are primarily associated with the phase of trial design, feasibility, and country eligibility. Low recruitment rate was related to the selection of sites and/or countries with lack of infrastructure and difficult communication (5). These factors led to insufficient scientific evidence for labeling and/or adjusting clinical use of drugs, resulting in a persistently high off-label drug use in children (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the utility of site identification summaries, a strategy set up by the BPCRN and piloted by BPCRN and Pedmed-NL, was found to be beneficial for sponsors through direct communication and coherence with potential site selection. Conducting high-quality clinical trial feasibilities and setting expectations, especially in a pediatric setting, has been shown as a key investment to ensure successful trial execution (5,18,20). To date, there are no published or publically available metrics to compare a site identification process within a research network setting.…”
Section: Discussionmentioning
confidence: 99%
“…IST primarily focuses on obtaining drug approval from regulatory authorities, whereas IIRs/IITs aim to explore scientific value and address specific clinical questions, [ 1 ] including rare diseases, comparative diagnostics or treatments, novel uses for approved drugs, new indications, or innovative administration methods. [ 2 , 3 ] Clinical studies can employ noninterventional (prospective or retrospective) or interventional research methods. One key advantage of IIRs/IITs is its origin from real clinical problems encountered in daily practice, allowing investigators to have greater autonomy and a closer connection to practical aspects of medicine.…”
Section: Introductionmentioning
confidence: 99%